KOMPETENSI, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS TENAGA KERJA OPERASIONAL BAGIAN MEKANISASI (Studi Pada PT Senang Kharisma Text 2 Di Sukoharjo) - Reksi Pradikta Ade (EKOBIS, 2019)
Competition in the global market is so tight, companies are trying to meet market demand. To meet the huge market needs, companies are required to meet the increasing market demand. Large demand will be followed by large quantities of production supported by maintenance of tools and production machinery. The study was conducted to examine the effect of competencies, organizational culture and work discipline on the productivity of the operational workforce in the mechanization section (study on pt. Senang kharisma text 2 in sukoharjo). 50 sample research samples. multiple linear regression method. The results of competency research, organizational culture and work discipline simultaneously have a significant effect on the productivity of the operational workforce in the mechanization section and in terms of competency, organizational culture and work discipline each have a positive and significant effect on the productivity of the operational workforce in the mechanization section. the productivity of the operational workforce in the mechanization section can be explained by three independent variables at 54.4% and the other 45.6 influenced by other variables. Keywords: competence, organizational culture and work discipline